AJENG’S PERSONAL BRANDING WAS WAITED AS INDIKA FM RADIO ANNIVERSARY THROUGH TIKTOK SOCIAL MEDIA - Nadila, Syarifah; Rajagukguk, Djudjur Luciana (Journal of Social Political Sciences, 2022)
This study aims to determine the application of Ajeng Dinanti’s personal branding as an Indika FM radio announcer through Tiktok social media. The theory used in this study is Peter Montoya’s theory, namely 8 laws of personal branding or 8 concepts for the formation of great personal branding consisting of specialization, leadership, personality, difference, appearance, unity, firmness, and good name. This research method is qualitative with a descriptive approach, where the researcher explains in detail how the application of Ajeng Dinanti’s personal branding as an Indika FM radio announcer through Tiktok social media, with 3 informants selected purposively, namely 1 key informant, namely Ajeng Dinanti’s Tiktok account follower, Abdu, then 2 informants, namely Ajeng Dinanti herself as the person who applies personal branding and listeners from Indika FM in the Indika Sewing program, namely Dwi Septianingsih. The findings of this study show that the fulfillment of specialization is reflected in Ajeng’s personal branding as a radio announcer. Personality is reflected in the way Ajeng stays true to herself in implementing her personal branding. Then on the difference, it is very visible that Ajeng has a different way of implementing her personal branding with other broadcasters. Then there is an appearance, it is clear that Ajeng did this personal branding so that the public could see that Ajeng is an Indika FM radio announcer. Then the unity, personal branding that Ajeng does hopes that she can become the audience’s top of mind. Then there is determination, in carrying out his personal branding, Ajeng is consistent in sharing content on her Tiktok social media. Then finally there is a good name, by doing this personal branding, finally many people know that Ajeng is an announcer from Indika FM radio. Then, when viewed from the side of the researcher, the concept of specialization dominates. It can be concluded that the application of Ajeng Dinanti’s personal branding as an Indika FM radio announcer through Tiktok social media has been successful, although there is one element that is not fulfilled..